Female labor force participation under the pandemic: evidence from the 2020 Uganda High-Frequency Phone survey on COVID-19 - James Mukoki; Douglas Candia Andabati; Ibrahim Mukisa; Edward Musoke (Cogent Business & Management, 2024)
This study was designed to investigate the impact of COVID-19 lockdown measures and their associated self-reported threats on female labor force participation (FLFP) in Uganda following the March 20th, 2020 shutdown of the economy by the government. The interest in women in this study stems from the fact that despite the economic activity shutdown, women's work and roles extend even to their homes. The participation of women in the labor force is a significant factor in the development and growth of society. It is also worth acknowledging that in developing nations like Uganda, women join the workforce as a coping strategy for shocks (i.e. COVID-19 pandemic) and also because of poverty. Therefore, using the Uganda High-Frequency Phone Survey on the Coronavirus Disease 2019 (i.e. COVID-19) pandemic (UHFS) data set. That was collected by the Uganda Bureau of Statistics (UBOS) immediately after the government instituted strict lockdown measures, our results indicated a 17% reduction in FLFP especially in the early days of the economic shutdown. The findings also indicated larger effects on female labor market activities in case of extreme lockdown when both partners were locked down (i.e. both stayed home at the same time). However, the impact of lockdown was more pronounced than the self-reported COVID-19 threat among women with children as opposed to those without children. We also find larger predicted probabilities for female labor market participation for those employed than those unemployed as the pandemic evolved. Given the above results, our results are somewhat consistent with the famous household labor supply theories. As a policy direction, the government should institute a gender-sensitive pandemic response social support plan. This would enable the government to compensate women for the double burden (i. e. formal employment loss and increased unpaid household work) suffered during such pandemic outbreaks in future.Our research delves into a critical aspect of the COVID-19 pandemic's impact: the participation of women in the labor force in Uganda. Through the lens of the 2020 Uganda High-Frequency Phone Survey on COVID-19, we aim to uncover the unique challenges and opportunities faced by Ugandan women during this unprecedented time. By analyzing this data, we hope to shed light on how the pandemic has influenced women's ability to engage in economic activities, support their families, and contribute to the nation's development. Our findings offer insights into the immediate effects of the pandemic but also provide valuable information for policymakers, organizations, and individuals striving to create a more equitable and resilient society for women in Uganda and beyond.
Keywords: I12; J01; J50; J64; 650; Female labor force participation; COVID-19 threat; lockdown; coronavirus outbreak; uganda High-Frequency phone survey